Peran Pendidikan Pertahanan dalam Membangun Kesadaran Keamanan Nasional di Masyarakat - Deny Sujana Miharja; Cecep Sukrisna; Endang Purwaningsih (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
Defense education is strategic in building national security awareness among the public. This study aims to analyze the contribution of defense education in increasing public understanding of the importance of national security, as well as how it affects the attitude and behavior of citizens in facing threats with a qualitative method approach. In the context of globalization and increasingly complex threat dynamics, defense education is expected to be a means to strengthen the love of the homeland, awareness of the importance of unity, and community readiness to face various security challenges. The research method used is literature review and surveys to the public to measure the effectiveness of defense education programs. The results of the study show that through defense education, it is able to increase the sense of love for the homeland, awareness of security threats, participation in the active role of the community through strengthening unity and unity as well as readiness in facing global threats. Improving defense education at various levels of society is very important to realize sustainable national security.